An Inquiry into Self-Deception: Memento, Truth-Display, and the Detective Genre - Leblanc, Juliette (Intermédialités / Intermediality, 2023)
This article proposes to analyze the concept of self-deception in Christopher Nolan’s psycho-thriller film Memento (2000). Approached through the study of the senses and through a philosophical-semiological lense, the willing self-deception of the protagonist and misleading appearances central to the film’s narrative structure provoke an inquiry into the mechanics of truth and visual displacement. The protagonist’s memory-system sustains deceptiveness, which in turn allows one to conceptualize the structure of the story as a metanarrative of the detective genre.